Pemaknaan Struktur Penalaran Moral Anak pada Hikayat Kalilah dan Dimnah - Abda Billah Faza Muhammadkan Bastian; Dind Ibra Benign Sajid; Rina Febriana (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This study aims to map the structure of moral reasoning contained in the Hikayat Kalilah and Dimnah through Lawrence Kohlberg's moral development theory. The method used is qualitative with a literature study approach and content analysis techniques on the text of the saga. The results of the study indicate that the main moral values ​​in the saga are honesty, compassion, friendship, and hard work, which are represented through Kohlberg's three stages of moral reasoning: punishment-obedience orientation, relativist-instrumental orientation, and "good child" orientation. Each story contains a reasoning pattern that is appropriate to the child's cognitive development stage, where the concepts of punishment, reward, and social recognition become the driving force for moral action. These findings strengthen the potential of the Hikayat Kalilah and Dimnah as a children's reading material that is both entertaining and educational for the development of moral reasoning in early childhood. Thus, this hikayat is recommended to be integrated into learning materials aimed at instilling moral values.